360 Degrees of Pressure: The Changing Role of the HR Professional in the Hospitality Industry. (May 2015) - Solnet, David; Kralj, Anna; Baum, Tom
Many hospitality companies highlight the importance of their employees, and this features strongly in their consumer marketing. However, the capacity of organizations to deliver "people first" practices is seemingly subject to increasing pressure within the international hospitality sector, both internally and from the external environment. Nowhere is this clearer than in the roles that are played with respect to the human resource management (HRM) function, both by those specifically designated in that post and by nonspecialist managers taking HRM responsibilities. This conceptual article has two principal aims: first, to illuminate the growing trend of formalized HRM practices being downgraded, eliminated altogether, or decentralized; and second, to highlight the need for a greater understanding and consideration of the external factors affecting hospitality HRM practice. The article reviews the nature and scope of the HRM function in hospitality, presents an overview of the trends toward internal reorganization through decentralization of HRM functions and, finally, assesses the impact of external pressures of the delivery of effective HRM. We then propose a dynamic framework designed to help facilitate greater understanding of the implications of internal and external pressures by HRM professionals and researchers, and conclude with reflections and recommendations followed by proposals for future research.